Proceedings of the Twenty-First Annual ACM-SIAM Symposium on Discrete Algorithms 2010
DOI: 10.1137/1.9781611973075.111
|View full text |Cite
|
Sign up to set email alerts
|

SRPT is 1.86-Competitive for Completion Time Scheduling

Abstract: We consider the classical problem of scheduling preemptible jobs, that arrive over time, on identical parallel machines. The goal is to minimize the total completion time of the jobs. In standard scheduling notation of Graham et al. [5], this problem is denoted P | rj, pmtn | P j cj . A popular algorithm called SRPT, which always schedules the unfinished jobs with shortest remaining processing time, is known to be 2-competitive, see Phillips et al. [13,14]. This is also the best known competitive ratio for any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…We also provide improved general lower bounds of 21/19 ≈ 1.105 and 1.114 on the competitive ratio of any deterministic algorithm for the problems P | r j , pmtn | j c j and P | r j , pmtn | j w j c j , respectively. We believe that 21/19 is the correct answer for the unweighted problem, as we agree with the conjecture of [11] that the algorithm SRPT is 21/19-competitive.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We also provide improved general lower bounds of 21/19 ≈ 1.105 and 1.114 on the competitive ratio of any deterministic algorithm for the problems P | r j , pmtn | j c j and P | r j , pmtn | j w j c j , respectively. We believe that 21/19 is the correct answer for the unweighted problem, as we agree with the conjecture of [11] that the algorithm SRPT is 21/19-competitive.…”
Section: Resultssupporting
confidence: 85%
“…We prove these lower bounds by giving a simple scheme for constructing an instance where the nature of the jobs that arrive depends on the choices the algorithm has made so far. The scheme is based on the lower bound instance for the algorithm SRPT, from [11]. Theorem 1.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a new idea is needed to prove a smaller ratio. Indeed, the proof by Chung et al [5] is completely different and uses a sophisticated randomized analysis of the optimal solution. On the contrary, our proof builds on the original proof of Phillips et al and continues where that proof stops.…”
Section: The Competitive Ratio Of Srptmentioning
confidence: 99%
“…The example in Figure 1 shows that this is not true when SRPT is applied to parallel machines. The best known upper bound on its competitive ratio was 2 [16] until recently (SODA2010), Chung et al [5] showed that the ratio is at most 1.86. Moreover, they show that the ratio is not better than 21/19 > 1.105.…”
Section: Introductionmentioning
confidence: 99%